Briefnetz Leopoldina : die Korrespondenz der Deutschen Akademie der Naturforscher um 1750 - Mücke, Marion (Walter de Gruyter, 2009)
On the one hand this book presents unique source material about the history of the Academy Leopoldina and on the other it serves to extend our knowledge in the fields of medicine and history of science. The reader is given an insight into the way the sciences at the time were organized and the book poses the question whether scientific communication through virtual networks started as early as the eighteenth century.